n(8n-5)=0

Simple and best practice solution for n(8n-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n(8n-5)=0 equation:


Simplifying
n(8n + -5) = 0

Reorder the terms:
n(-5 + 8n) = 0
(-5 * n + 8n * n) = 0
(-5n + 8n2) = 0

Solving
-5n + 8n2 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), 'n'.
n(-5 + 8n) = 0

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0

Subproblem 2

Set the factor '(-5 + 8n)' equal to zero and attempt to solve: Simplifying -5 + 8n = 0 Solving -5 + 8n = 0 Move all terms containing n to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 8n = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 8n = 0 + 5 8n = 0 + 5 Combine like terms: 0 + 5 = 5 8n = 5 Divide each side by '8'. n = 0.625 Simplifying n = 0.625

Solution

n = {0, 0.625}

See similar equations:

| 4(2e+5)=0 | | 5n(5n+6)=0 | | (3x+9)(2x-10)=0 | | 9x+2=4x | | 7a+6=6b+5 | | 6u^2+3u+2=0 | | x^2+17=7x+5 | | (7+9)+11=(9+7)+11 | | (x+3)(2x-7)+9=(2x-7)(x+3)+9 | | 9(x+2)-8=10 | | f=i-gt | | 6x+1+6x+2=42 | | (n+2)[(n+2)-9]=18 | | (n+2)((n+2)-9)=18 | | (n+2)((n+2)-9)=0 | | [8+(-8)]+w=0+w | | 8x-3=1-2x | | 1/x=(x+1)/6 | | 4x^3-9x^2-18x=0 | | x^2-13x+6=-9x+3 | | x^2+11x+28=10 | | 5x^4+24x^2+2=0 | | 1x+-1=12 | | 3000-x=9000 | | 100=x+(x+5)+(x*3) | | 21x+35y=28 | | 21x+3y=28 | | 4(x-2)-6=6-(x+5) | | 3w+6=2w-1 | | (2x-5)*(2-x)= | | -5-7s=-6 | | 2x^2+5x-83.5=0 |

Equations solver categories